Streptococcus equi subsp. zooepidemicus Invades and Survives in Epithelial Cells - Skive, Bolette; Rohde, Manfred; Molinari, Gabriella; Braunstein, Thomas Hartig; Bojesen, Anders M. (Frontiers in Cellular and Infection Microbiology, 2017)
Streptococcus equi subsp. zooepidemicus (S. zooepidemicus) is an opportunistic pathogen of several species including humans. S. zooepidemicus is found on mucus membranes of healthy horses, but can cause acute and chronic endometritis. Recently S. zooepidemicus was found able to reside in the endometrium for prolonged periods of time. Thus, we hypothesized that an intracellular phase may be part of the S. zooepidemicus pathogenesis and investigated if S. zooepidemicus was able to invade and survive inside epithelial cells. HEp-2 and HeLa cell lines were co-cultured with two S. zooepidemicus strains (1-4a and S31A1) both originating from the uterus of mares suffering from endometritis. Cells were fixed at different time points during the 23 h infection assay and field emission scanning electron microscopy (FESEM) was used to characterize adhesion and invasion mechanisms. The FESEM images showed three morphologically different types of invasion for both bacterial strains. The main port of entry was through large invaginations in the epithelial cell membrane. Pili-like bacterial appendages were observed when the S. zooepidemicus cells were in close proximity to the epithelial cells indicating that attachment and invasion were active processes. Adherent and intracellular S. zooepidemicus, and bacteria in association with lysosomes was determined by immunofluorescence staining techniques and fluorescence microscopy. Quantification of intracellular bacteria was determined in penicillin protection assays. Both S. zooepidemicus strains investigated were able to invade epithelial cells although at different magnitudes. The immunofluorescence data showed significantly higher adhesion and invasion rates for strain 1-4a when compared to strain S31A1. S. zooepidemicus was able to survive intracellularly, but the survival rate decreased over time in the cell culture system. Phagosome-like compartments containing S. zooepidemicus at some stages fused with lysosomes to form a phagolysosome. The results indicate that an intracellular phase may be one way S. zooepidemicus survives in the host, and could in part explain how S. zooepidemicus can cause recurrent/persistent infections. Future studies should reveal the ability of S. zooepidemicus to internalize and survive in primary equine endometrial cells and during in vivo conditions.